The american interwar foreign policy and a “New world - AHOUANGANSSI, SÈNAKPON RAOUL (My University, 2016)
This paper stands as an endeavor to examine and help grasp the very insights of the American foreign policy between the two world wars. Within the angle of a new world order, this policy clearly sets out the highly wished hope of a world of a more liberal and democratic place regulating interactions among nations. Requiring a global reach out of a suitable plan, an active personality behind it and a strong-willed framework of accurate visions, the foreign policy put in place met the challenges only partially and unsteadily. The American perception of world outside meaning, the fits and starts about what foreign policy should impulse to, the evidence of selfishness and missteps represent in one word, the lineaments of the interwar diplomatic policy in line with what the American historiography reveals from its in-depths.
Keywords: Foreign policy; new world order; challenge; interwar; historiography